MicroRNA-based therapeutics in cardiovascular disease: screening and delivery to the target. (1st December 2017) - Mellis, David; Caporali, Andrea
Abstract : MicroRNAs (miRNAs) are small non-coding RNAs of ∼22 nucleotides, which have increasingly been recognized as potent post-transcriptional regulators of gene expression. MiRNA targeting is defined by the complementarities between positions 2–8 of miRNA 5′-end with generally the 3′-untranslated region of target mRNAs (messenger RNAs). The capacity of miRNAs to simultaneously inhibit many different mRNAs allows for an amplification of biological responses. Hence, miRNAs are extremely attractive targets for therapeutic regulation in several diseases, including cardiovascular. Novel approaches are emerging to identify the miRNA functions in cardiovascular biology processes and to improve miRNA delivery in the heart and vasculature. In the present study, we provide an overview of current studies of miRNA functions in cardiovascular cells by the use of high-content screening. We also discuss the challenge to achieve a safe and targeted delivery of miRNA therapeutics in cardiovascular cells.